Feasibility of electromechanical basic work e-module as a new learning media for vocational students - Mustofa Abi Hamid; Lely Yuliawati; Didik Aribowo (Intelektual Pustaka Media Utama, 2020)
This study aims to develop and determine the feasibility of E-Module learning media in Electromechanical Work Basic Subjects. This research is a development research using ADDIE model. The product developed is e-module learning media on subjects in Electromechanical Basic Work. Data collection is done by means of observation, interviews and questionnaires. The data analysis technique used in this research is descriptive analysis. This research was conducted on 128 students of 10th grade Department Electrical Installation Engineering in Vocational High School in Serang, Banten. The results of the research are Media validation is very feasible with a percentage of 95.3%. Material validation is very feasible with a percentage of 97.9%. The results of the questionnaire evaluation data of small group trials get an average percentage value of 91.7% and in the very feasible category. The results of the assessment in the large group trial data questionnaire received very decent results with a percentage of 92.4%. The results of the exercises carried out an average value of 92.1 before using learning media the average value obtained by students 80.5. The results of the evaluation scores get an average value of 88.5. The e-module learning media in Electromechanical Basic Work subjects can facilitate students in the learning process and facilitate the teacher in teaching.